Intra-cavitary radiotherapy for surgically resected brain metastases: a comprehensive analysis including an individual patient data meta-analysis of intraoperative radiotherapy (IORT) and brachytherapy (IBT) - Guranda, Alexandru; Güresir, Erdem; Ruder, Arne Mathias; Giordano, Frank Anton; Wach, Johannes (Journal of neuro-oncology, 2025)
Background Surgical resection followed by adjuvant radiotherapy is a standard approach for brain metastases (BM). Intracavitary radiotherapy techniques—namely intraoperative radiotherapy (IORT) and brachytherapy (IBT)—have gained attention as alternatives to stereotactic radiotherapy, potentially reducing neurotoxicity and treatment delays. However, robust comparative data remain scarce. Methods We performed a systematic meta-analysis including both conventional and reconstructed individual patient data (IPD) from studies reporting outcomes after intracavitary radiotherapy post-BM resection. Primary endpoint was local control rate (LCR); secondary endpoints included overall survival (OS), distant brain control (DBC), radiation necrosis (RN), and leptomeningeal disease (LMD). IPD was reconstructed from published Kaplan-Meier curves. Survival and incidence outcomes were pooled using random-effects models in R. Results Twenty-three studies with 858 patients were analyzed. The 1-year LCR was 96% (95% CI: 94-98%) for IORT and 95% (95% CI: 92-97%) for IBT. Median OS in patients who underwent IORT was 39.1 months (95% CI: 22.0-59.5), and 15.9 months (95% CI: 12.6-19.9) in whose who underwent IBT, respectively (p = 0.004; HR 0.64). IORT was associated with lower RN (4% vs. 7%) and LMD (6% vs. 9%). The 1-year DBC rate was higher for IORT (57%) than IBT (48%). Conclusions Intracavitary radiotherapy yields excellent local control after BM resection. This IPD meta-analysis provides the most comprehensive evidence to date and supports further prospective evaluation of IORT in neuro-oncological care. Graphical abstract
Online veröffentlicht: 17. September 2025
Gesehen am 16.10.2025